Bargaining power, decision making, and biofortification: The role of gender in adoption of orange sweet potato in Uganda - Gilligan, Daniel O.; Kumar, Neha; McNiven, Scott; Meenakshi, J. V.; Quisumbing, Agnes R. (Elsevier, 2020)
We examine the role of gender dimensions of intrahousehold bargaining power and decision making in the adoption and diffusion of orange sweet potato (OSP), a biofortified crop being promoted to increase dietary intakes of vitamin A in Uganda. We use patterns of ownership and control of land and other assets by married men and women to create gender-disaggregated indicators of bargaining power, allowing for joint and sole ownership and control of land and assets. Using data from an experimental evaluation of a project promoting OSP adoption, we find that the probability of adopting OSP is not affected by the exclusive or joint control of assets by women at the household level. However, within households, parcels of land under joint control, in which the woman has primary control over decision making, are significantly more likely to contain OSP. Women who control a higher share of household nonland resources are more likely to share OPS vines, showing that women use greater bargaining power to facilitate diffusion of this health-promoting technology. We do not find any impact of women’s bargaining power on children’s dietary intakes of Vitamin A, possibly because husbands and wives have the same preferences regarding their children’s nutritional status. These results contribute to reshaping our understanding of household decision making to inform the design and implementation of agriculture-nutrition interventions.